2016
DOI: 10.1007/s00477-016-1236-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of complexity on daily and multi-step forecasting of streamflow with chaotic, stochastic, and black-box models

Abstract: Despite significant research advances achieved during the last decades, seemingly inconsistent forecasting results related to stochastic, chaotic, and black-box approaches have been reported. Herein, we attempt to address the entropy/complexity resulting from hydrological and climatological conditions. Accordingly, mutual information function, correlation dimension, averaged false nearest neighbor with E1 and E2 quantities, and complexity analysis that uses sample entropy coupled with iterative amplitude adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 99 publications
0
16
0
1
Order By: Relevance
“…If the calculated c e is unchanged by increasing the number of embedding dimensions, C e can be considered as the correlation dimension of the attractor in the system. But, if c e is not stable as a function of embedding dimensions, this system can be considered non-chaotic [54,96,97].…”
Section: Correlation Dimensionmentioning
confidence: 99%
“…If the calculated c e is unchanged by increasing the number of embedding dimensions, C e can be considered as the correlation dimension of the attractor in the system. But, if c e is not stable as a function of embedding dimensions, this system can be considered non-chaotic [54,96,97].…”
Section: Correlation Dimensionmentioning
confidence: 99%
“…Furthermore, Hu et al (2001) and Tongal and Berndtsson (2016) perform multi-step ahead forecasting of time series without seasonal behaviour.…”
Section: Time Series Forecasting In Hydrology and Beyondmentioning
confidence: 99%
“…Similarly, Yu et al (2004) compare several forecasting methods, including an ARIMA model and SVM, on two daily time series of runoff and Tongal and Berndtsson (2016) compare several stochastic and ML forecasting methods on three time series of streamflow processes. Additionally, in Chen et al (2012) the reader can find one of the few studies using RF for hydrological forecasting tasks.…”
Section: Right After the Introduction Of The Currently Classical Automentioning
confidence: 99%
“…Studies have also found that AR models were quite competitive with the complex nonlinear models including k-nearest neighbor and ANN models. (Tongal and Berndtsson 2016). In this regard, the significant flow persistence represents an important feature in flood forecasting and the AR(2) model is simple enough, while capturing the flow persistence, to suffice a bench mark series.…”
Section: Uncertainties In Mpe Criteriamentioning
confidence: 99%